Fixation of the intraocular lens SL-907 CENTRIX DZ in the lenticular sac fenestra as a result of anterior and posterior capsulorrhexis - D.G. Zhaboiedov (Ukrainian Society of Ophthalmologists, 2015)
Introduction. Despite the considerable improvement and general practical application of high-tech techniques in cataract surgery, in the late postoperative period 4.5-20% of cases are complicated by the secondary cataract that motivates to a further search of new and more effective methods of its development preventing. Objective is to study the effectiveness of the method of IOL SL-907 Centrix DZ fixation at capsulorrhexis edges for preventing the secondary cataract development. Materials and methods. 35 patients were examined during the study. They were implanted IOL SL-907 Centrix DZ after senile cataract phacoemulsification. It was fixed at the edges of anterior and posterior capsulorrhexis so that 2 haptic elements were located at the posterior capsule edge and the other two at the anterior capsule edge. In this case, capsulorrhexis edges were located between haptic elements and the optical part was located directly above the hyaloids membrane. Results and discussion. All the patients had no complications during the postoperative period. The control examination in 6 months after the implantation showed a revealed stability of the implanted IOL in all cases. Three years after the surgery, the routine examinations showed no IOL dislocation and decentration, as well as the signs of the opacity; the vision of the patients remained stable. Visual acuity averaged 0.7±0.2. IOP indicators were within the normal range (13-17 mm Hg). Conclusions. Thus, the developed IOL SL-907 Centrix DZ fixation method at the fenestra of anterior and posterior capsulorrhexis has proved to be effective as in terms of fixation reliability, as in terms of prevention of secondary cataract development.